Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 10614 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Aves", "Country is Mozambique", "Year is less than or equal to 1971" ] } The dataset includes 10614 records from 32 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005237-170627171947987/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences